Oncolytic viruses: strategies, applications and challenges - Russell, Stephen J. (Henry Stewart Talks, 2023)
Measles, Vesicular stomatitis virus, Picornavirus, Herpesvirus, Coxsackievirus, Cytomegalovirus, Modified Measles Virus (MV-NIS), T cell lymphoma, Clinical trials, Voyager-V1, Talimogene laherparepvec (T-VEC)